THE OCCURRENCE OF CAFESTOL AND KAHWEOL DITERPENES IN DIFFERENT COFFEE BREWS - Novaes, Fábio Junior Moreira; Bayan, Fernanda Calvente; Aquino Neto, Francisco Radler; Resende, Claudia Moraes (Coffee Science - ISSN 1984-3909, 2019)
Coffee is the second most consumed brew in the world, after water. Cafestol and kahweol are two diterpenes that have been identified, until now, exclusively in the coffee tree. They are co-extracted from the coffee beans that are roasted and ground for the beverage preparation. Their pharmacological properties are related to anticancer and anti-inflammatory activities, although they also increase the serum cholesterol. Several researches reported that coffee brew preparation methods influence directly the levels of the diterpenes. This paper describes a compilation of the main results published for different coffee brews and all variables related to their preparation. Major differences in the reported concentrations have been noted.